MPLEMENTASI SLIP GAJI ELEKTRONIK DALAM RANGKA MENJANGKAU LOKASI KARYAWAN YANG BERTUGAS DI BERBAGAI LOKASI - Poetryono, Djati; Broto, Satrio (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2015)
Pay  slips  provided  by  the  company  to  employees  as  a  sign  written  evidence  that  the company has been paying the salaries of employees according to applicable regulations. In paychecks There are two areas, namely the area of income and area of the deduction. The difference between the two in the form of salary to  be net received by employees. If company has a lot of work location, distribution of slip salaries in a timely manner to all employees to be something important. Delays in the receipt paychecks by employees in the  field  location  can  cause  problems  for  the  company.  By  utilizing  information technology,such potenstial problem could be reduced significantly.